Sipakatau as a Model for Conflict Resolution in Village Head Elections in Luwu Regency, South Sulawesi - Armin, Rizka Amelia; Adliyah, Nurul; Putra, Andi Alamsyah Perdana (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
Conflicts in village head elections are a recurring phenomenon within the dynamics of local politics in Indonesia. In Luwu Regency in 2022, several villages experienced tensions among supporters of competing candidates. Interestingly, some of these conflicts were not resolved through formal legal mechanisms but instead relied on the local wisdom of the Luwu community, namely the Sipakatau philosophy. This study aims to analyze how the humanistic values of Sipakatau are operationalized in resolving electoral disputes at the village level, as well as to highlight its advantages compared to formal mechanisms that tend to be legalistic. The research employed a qualitative phenomenological approach, utilizing observation, in-depth interviews with community leaders, religious figures, and village officials, as well as literature review. Data analysis was carried out descriptively to interpret the practice of Sipakatau in conflict resolution. The findings indicate that the operational mechanism of Sipakatau is manifested through tudang sipulung (deliberative forums), communal cooperation, and socio-religious activities involving all elements of the community. This mechanism emphasizes respect for human dignity, togetherness, and reconciliation without the domination of any single party. The study reveals that Sipakatau is not merely a cultural tradition but also a contextual and effective conflict resolution model that contributes to maintaining the stability of local democracy. The research concludes that local wisdom plays a strategic role in building post-election harmony and has the potential to serve as a policy reference for resolving political conflicts at the village level.